2015
DOI: 10.1016/j.biopsycho.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

The functional role of individual-alpha based frontal asymmetry in stress responding

Abstract: Asymmetry in frontal electrical activity has been suggested to index tendencies in affective responding and thus may be associated with hormonal stress responses. To assess the functional role of frontal asymmetry (FA) in stress, we measured FA at rest and following exposure to acute stress induced with the Maastricht Acute Stress Task (MAST; N=70) in the standard 8-13Hz band as well as based on individual alpha frequency (IAF) band. IAF-based resting FAF4-F3 was associated with the stress-induced neuroendocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 54 publications
(23 reference statements)
7
75
0
Order By: Relevance
“…The decrease in alpha rhythm on the PFC obtained in this study is consistent with previous emotional and anxiety studies and with studies that injected cortisol to human subjects [42][43][44][45]. Additionally, the difference in activities of the right and left PFC in this study is in line with previous EEG study that showed hemispheric difference under stress condition [46]. This result suggests that cortical activities shifted from diffused to focal under stress condition.…”
Section: Discussionsupporting
confidence: 92%
“…The decrease in alpha rhythm on the PFC obtained in this study is consistent with previous emotional and anxiety studies and with studies that injected cortisol to human subjects [42][43][44][45]. Additionally, the difference in activities of the right and left PFC in this study is in line with previous EEG study that showed hemispheric difference under stress condition [46]. This result suggests that cortical activities shifted from diffused to focal under stress condition.…”
Section: Discussionsupporting
confidence: 92%
“…Prior research has yielded mixed results regarding whether FAA acts as moderator or mediator, or both (Coan & Allen, ). Our results are in line with prior studies that have shown that frontal asymmetry moderates the effects of stressful life events (Davidson & Fox, ; Goodman, Rietschel, Costanzo, & Hatfield, ; Lopez‐Duran et al, ; Quaedflieg, Meyer, Smulders, & Smeets, ), and modulates responses to stressors (Lewis et al, ; Tops et al, ). Our results suggest that frontal asymmetry acts solely as moderator, and not a mediator, between maternal childhood trauma and child behavioral problems, and explains up to 35% of the variance.…”
Section: Discussionsupporting
confidence: 92%
“…This marker has been linked to current and lifetime depression, as well as to the prospective risk to develop depression (for review, see Allen and Reznik, 2015). Moreover, stronger left lateralized alpha at rest and in response to emotional provocation has been found to predict stronger mood decline and hormonal stress responses (Papousek et al , 2014; Quaedflieg et al , 2015). Furthermore, increased left-lateralized alpha following neurofeedback attenuates subjective habituation to laboratory stress induction (Quaedflieg et al , 2016).…”
Section: Introductionmentioning
confidence: 99%